In-situ growth of hollow NiCo layered double hydroxide on carbon substrate for flexible supercapacitor. (20th October 2019) - Xuan, Xiaoyang; Qian, Min; Han, Lu; Wan, Lijia; Li, Yuquan; Lu, Ting; Pan, Likun; Niu, Yueping; Gong, Shangqing
Abstract: Layered double hydroxides (LDHs) have shown remarkable potentials in supercapacitors for their highly-redox capacitance. However, the poor contact with substrate, slow charge transfer and ion diffusion, and low electrical conductivity limit their capacitor performance. In this work, a flexible free-standing supercapacitor was designed, with in-situ grown hollow-structured NiCo layered double hydroxide (H–NiCo LDH) as the active material based on a partial Ni ion substitution of Co ion in ZIF-67, and flexible carbon material as the substrate. Systematical investigation has been conducted in terms of nanostructures of the active material NiCo LDH (hollow or laminar structure) and flexible carbon substrates (acidified carbon cloth or acidified carbon fibers). A hollow-structured NiCo LDH@acidified carbon cloth (H–NiCo LDH@ACC) sample showed a promising capacity of 1377 mC/cm 2 (3060 mF/cm 2 ) at 1 mA/cm 2, a low charge transfer resistance of 0.15 Ω, a capacity retention of 70% and a coulombic efficiency retention of 99% upon 10, 000 cycles at 80 mA/cm 2 . PDMS-sealed solid-state H–NiCo LDH@ACC//AC devices were fabricated with an energy density of 0.0708 mWh/cm 2 at a power density of 0.7 mW/cm 2, with no obvious capacity decrease upon bending angles from 0° to 180°. SEM, EDS, XPS, and XRD analyses indicated the H–NiCo LDH has been in-situ grown on flexible carbon substrates. Hollow-structured LDH accelerated charge transfer and ion diffusion compared with a laminar-structured LDH. Acidified carbon cloth (ACC) showed better electrical conductivity compared with the biomass-derived acidified carbon fibers. Thus, a H–NiCo LDH@ACC is proposed as a promising candidate of a flexible supercapacitor. Graphical abstract: Image 1 Highlights: Hollow-structured NiCo layered double hydroxide (LDH) was in-situ grown on flexible carbon substrate for supercapacitor. Hollow-structured LDH accelerated charge transfer and ion diffusion compared with a laminar-structured LDH. Acidified carbon cloth showed better electrical conductivity compared with the acidified carbon fibers as substrate.